Relasi Kuasa dan Ketimpangan Gender: Diskriminasi terhadap Narapidana Perempuan di Lapas Kelas IIA Bojonegoro - Masyhar, Ahmad Nuriyan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study aims to discover the power relations in the correctional system and the manifestation of gender discrimination against female prisoners at the Bojonegoro Class IIA Correctional Institutions, focusing on access to reproductive health facilities, empowerment programs, and legal rights, including remission and parole. Although previous studies have examined the conditions of female prisoners in Indonesia, they have not specifically explored how gender dynamics operate in correctional institutions where women are a highly marginalized minority. This study fills that gap by analyzing how prison policies and institutional structures reinforce gender disparities. Data shows that female prisoners often face gender-based discrimination, particularly in accessing reproductive health services, which are severely limited due to the lack of specialized facilities, insufficient female medical staff, and budget constraints. Similarly, empowerment programs are often designed from a male-centric perspective, offering limited relevant options for women, with restricted access to training spaces, fewer female instructors, and inadequate resources. Furthermore, female prisoners receive remission and parole less frequently than their male counterparts, even when convicted of lesser offenses. Overcrowding further exacerbates these issues, restricting privacy, increasing reproductive health risks, limiting participation in empowerment programs, and straining already limited resources. The social and cultural stigma attached to female prisoners—who are often judged more harshly than men—adds another layer of discrimination, making it even harder for them to access their basic rights. Using Michel Foucault’s theory of power/knowledge and panopticism, this study discovers how prison policies and surveillance mechanisms reflect patriarchal power structures that place female prisoners in a subordinate position. The research findings highlight the urgent need for gender-responsive prison reforms, including improving reproductive health facilities, developing empowerment programs tailored to women's needs, and ensuring fairer legal treatment for female inmates. Additionally, regular policy monitoring is essential to creating a more equitable prison environment.